Dupuytren-Like Contracture of the Foot: Ledderhose Disease - Akdag, Osman (Surg J (N Y), 2016)
Introduction  Plantar fibromatosis is a rare hyperproliferative disease of plantar aponeurosis and is also called Ledderhose disease. Case properties and treatment are discussed in this report. Case Report  A 30-year-old man presented with painful bilateral plantar nodules. He had multiple and bilateral fixed and solid nodules on the plantar and medial side of his feet measuring 1 cm each. Ultrasound was performed and hypoechoic homogeneous nodules were detected. The patient underwent surgery, and the nodes were removed via a plantar incision with 2-cm safety distance. Discussion  Ledderhose disease is a rare, hyperproliferative disorder of the plantar aponeurosis. The nodules are slow growing and found in the medial part of the plantar fascia. The precise etiology remains unknown. The treatment options are conservative management, steroid injections, radiotherapy, and surgery. Conclusion  The main cause of this disease remains uncertain. Related conditions should be evaluated, and a patient who presents with Dupuytren or Peyronie disease should also be investigated for Ledderhose disease.